Application of Problem Based Learning Strategies to Overcome Students Learning Difficulties - Indayana Febriani Tanjung; Miftha Sandia Arilla; Putri Puspita Sari; Vira Putri Fadhilah (Universitas Muhammadiyah Enrekang, 2022)
This study aims to 1) describe the process of implementing Problem Based Learning (PBL) strategies in Biology subjects, on the Respiration System material for class XI and 2) to describe the results of implementing Problem Based Learning (PBL) methods in overcoming student learning difficulties in Biology subjects, in Class XI Respiratory System material. This research is a descriptive research. The research was carried out at SMA Negeri 5 Pematang Siantar, Siantar Martoba district, Pematang Siantar city in 2021/2022 as many as 33 students. The time of the research was carried out in the even semester of 2021/2022 in May 2022. The results obtained in this study were successfully carried out by applying a problem based learning learning strategy to overcome students' learning difficulties with an average score of 30 (very good category) at the first meeting. with details of the category grades 1 - 12 found as many as 2 students, for the category grades 12 -24 obtained as many as 8 students, then for the category values ​​​​24 - 36 found as many as 22 students and category values ​​36 - 48 found as many as 1 student and at the second meeting it was found the average score of 39 (very good category) with details of the value of 24 – 27 found as many as 27 students and the category value of 36-48 found as many as 6 students.